YOUNG REBELS, INDIGENOUS PEASANTS AND INSTALLATION SPEECH CLASSES IN THE FIELDS OF CAUTÍN. MOVIMIENTO CAMPESINO REVOLUCIONARIO. (CHILE 1967-1973) - Cárcamo Hernández, Ovidio (Revista de Historia Social y de las Mentalidades, 2024)
The purpose of this article is to analyze the route followed by some militants of the Movimiento de Izquierda Revolucionaria (MIR), in the framework of the Chilean Agrarian Reform from 1967 to 1973 in the province of Cautín, in southern of Chile. Furthermore we seek to describe the bonding process between the MIR and the indigenous peasantry relationship that was born on Movimiento Campesino Revolucionario (MCR) in the late 1970s, starting a major crackdown on big land ownership, which buzzed local employer groups, at least until the 1973 military coup. Moreover, we sought to characterize those young people mostly from the urban middle class, whose delivery MIR allowed to create a mass front, rare in agrarian history of Chile.